2016
DOI: 10.1371/journal.pone.0158590
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Brain: Knowledge in Research Works and Neuron Activity

Abstract: If the market has an invisible hand, does knowledge creation and representation have an “invisible brain”? While knowledge is viewed as a product of neuron activity in the brain, can we identify knowledge that is outside the brain but reflects the activity of neurons in the brain? This work suggests that the patterns of neuron activity in the brain can be seen in the representation of knowledge-related activity. Here we show that the neuron activity mechanism seems to represent much of the knowledge learned in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Then delete this minutia from sample, so it won't show up in other models either. And turn to step (6). Otherwise, these two are not the same, and turn to step (5).…”
Section: Algorithmmentioning
confidence: 99%
“…Then delete this minutia from sample, so it won't show up in other models either. And turn to step (6). Otherwise, these two are not the same, and turn to step (5).…”
Section: Algorithmmentioning
confidence: 99%
“…"Invisible brain" suggests the idea that there are different domains where knowledge processing occurs [42]. Prior work identified that there is an additional layer of knowledge processing between the neuron network system and the brain [43,44].…”
Section: Invisible Brainmentioning
confidence: 99%
“…The basic units of our nervous system are the neurons which have a body cell, dendrites with receiving function and an axon with conductive function. Neurons are seen as cells specialized in communication either with other neurons or with other kinds of cells [6].…”
Section: Human Brainmentioning
confidence: 99%